Management of Diabetes Care Services (Journal of Chittagong Medical College Teachers' Association, 2018)
Diabetes is a chronic metabolic disorder with short and long term consequences which requires prompt treatment sometimes even with prolonged hospitalization and increased health care costs. It is thus very important to have an effective and efficient Diabetes Multi- Specialty Health Care team to ensure early detection and prevention of complications in every Diabetes Centre. Diabetes Self-Management Education (DSME) is an invaluable tool that is associated with improved diabetes knowledge and self-care behavior, improved clinical outcomes such as lower HbA1C, lower self-reported weight, improved quality of life; healthy coping; and lower costs and thus needs to be implemented and educated to every patient. Moreover, the Diabetes educator also has an important role to teach about diabetes and self management so that patients can carry out their own part of the responsibility. Educators help patients reflect on their own personal situation and priorities so that they will be prepared to make informed decisions to reach their diabetes goals. Furthermore, noncompliance of treatment amongst patients and the detrimental effects of Poly pharmacy on the patient’s well-being also need to be addressed to minimize complications. Lastly, an effective patient register and recall system are crucial components of successful diabetes care within a general practice setting and a dynamic and regular process of audit is necessary to identify deficiencies and ensure improvements in practice.JCMCTA 2018 ; 29 (1) : 68-74